Personal Politics without Clientelism? Interpreting Citizen-Politician Contact in Africa. (30th April 2018) - Mueller, Lisa
Abstract: This study clarifies the meaning of clientelism and documents its extent in sub-Saharan Africa—a region that political scientists and policy makers often view as especially clientelistic. It proposes an understanding of clientelism as personal contact between citizens and politicians in which citizens request selective rather than public goods in exchange for political loyalty. It then suggests that assessments of clientelism in Africa are sensitive to the amount of information about personal contact that surveys provide. Closed-ended Afrobarometer surveys suggest that personal contact is mostly clientelistic, whereas the original open-ended questionnaires employed in an original survey from Niger suggest that the bulk of citizen requests are programmatic. Leveraging detail in Nigeriens' qualitative accounts of visiting and calling politicians, the highly personalized contact of Nigeriens can be understood as an adaptation to limits on impersonal contact, not a sign that politicians are circumventing formal channels of communication in order to distribute patronage under the table. Résumé: Cette étude clarifie la signification du clientélisme et documente son étendue dans L'Afrique saharienne - une région que les politologues et dirigeants considèrent souvent comme particulièrement clientéliste. Il propose une compréhension du clientélisme en tant que contact personnel entre les citoyens et les politiciens dans lequel les citoyens demandent des biens sélectifs plutôt que publics en échange d'une loyauté politique. Il suggère ensuite que les évaluations du clientélisme en Afrique sont sensibles à la quantité d'informations sur les contacts personnels fournis par les enquêtes. Les enquêtes Afrobaromètre fermées suggèrent que le contact personnel est principalement clientéliste, alors que les questionnaires initiaux ouverts dans une enquête originale du Niger suggèrent que la majorité des demandes des citoyens sont programmatiques. Le contact hautement personnalisé des Nigériens peut être compris comme une adaptation aux limites du contact impersonnel, pas un signe que les politiciens contournent les voies officielles de communication afin de distribuer le mécénat sous la table.